Analisis Faktor yang Dipertimbangkan Siswa PKBM Se-Surakarta dalam Keputusan Memilih Melanjutkan Studi di Perguruan Tinggi - Purbiyanto, Eko; Pratiwi, Riszki Wijayatun; Santosa, Tri Budi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was (1) to determine the factors considered by PKBM students throughout Surakarta in determining whether to continue their studies at university and (2) to determine the dominant factors considered by PKBM students throughout Surakarta in determining whether to study at university. This study was quantitative with a descriptive design. The population in this study were all PKBM students throughout Surakarta, totaling 510 students. The research sample consisted of 31 respondents selected using purposive sampling technique, namely PKBM students who were at the equivalent of high school education level and had the potential or desire to continue their studies at university. The data were analyzed using factor analysis. The results of the study showed that (1) there were five factors considered by PKBM students throughout Surakarta in determining whether to study at university, namely product, process, physical evidence, price, and personality, and (2) the most dominant factor considered by PKBM students throughout Surakarta in determining whether to study at university was product quality